How to be eaten eaudiobook A novel. - Adelmann, Maria (2022)
One of NPR's Best Books of the Year: This darkly funny and provocative novel reimagines classic fairy tale characters as modern women in a support group for trauma. In present-day New York City, five women meet in a basement support group to process their traumas. Bernice grapples with the fallout of dating a psychopathic, blue-bearded billionaire. Ruby, once devoured by a wolf, now wears him as a coat. Gretel questions her memory of being held captive in a house made of candy. Ashlee, the winner of a Bachelor-esque dating show, wonders if she really got her promised fairy tale ending. And Raina's love story will shock them all. Though the women start out wary of one another, judging each other's stories, gradually they begin to realize that they may have more in common than they supposed . . . What really brought them here? What secrets will they reveal? And is it too late for them to rescue each other? ​Dark, edgy, and wickedly funny, this debut for readers of Carmen Maria Machado, Kristen Arnett, and Kelly Link takes our coziest, most beloved childhood stories, exposes them as anti-feminist nightmares, and transforms them into a new kind of myth for grown-up women. *Belletrist June Book Club Pick* Named a Best Book of May by TIME Magazine & Glamour One of NPR's Best Books of the Year